2022
DOI: 10.1108/rsr-03-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Tracking student learning outcome engagement at the reference desk to facilitate assessment

Abstract: PurposeThis paper presents a novel approach to associating patron interactions with specific student learning objectives (SLOs) incorporated into reference transactions in an environment where learning, as opposed to usage or user satisfaction data, is considered a benchmark of success.Design/methodology/approachAs part of the routine process of recording reference transactions into a tracking database, reference librarians associated each of their patron interactions with library programmatic SLOs they percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In support of these findings, several studies have shown positive effects on student engagement when assessments were offered [34] and when teamwork was implemented in extensive enrollment courses [35]. Similarly, Current [36] emphasized the need for feedback in formative assessments to evaluate teaching and learning systems, while Geletu [37] found that teacher participation positively affects students' learning engagement in science. Ma and Luo [38] demonstrated that engaging in student and peer assessment can positively impact learning performance, and Kim et al [39] showed that clustering algorithms could effectively assess student engagement in asynchronous online learning.…”
Section: Student Engagement In Learningmentioning
confidence: 91%
“…In support of these findings, several studies have shown positive effects on student engagement when assessments were offered [34] and when teamwork was implemented in extensive enrollment courses [35]. Similarly, Current [36] emphasized the need for feedback in formative assessments to evaluate teaching and learning systems, while Geletu [37] found that teacher participation positively affects students' learning engagement in science. Ma and Luo [38] demonstrated that engaging in student and peer assessment can positively impact learning performance, and Kim et al [39] showed that clustering algorithms could effectively assess student engagement in asynchronous online learning.…”
Section: Student Engagement In Learningmentioning
confidence: 91%